News Balance Rhetoric: The Fraser Institute’s Political Appropriation of Content Analysis - Hackett, Robert A. (Canadian Journal of Communication, 1992)
The Fraser Institute’s bulletin On Balance, which offers monthly content analyses of news, is critically examined. Methodological, conceptual and epistemological problems are discussed, as well as a rhetorical mode of reporting results which implies a politicized interpretation of news.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjE5OTJ2MTduMWE2NDY